Conceptualizing a Sustainable Food System in an Automated World: Toward a “Eudaimonian” Future - Shepon, Alon; Henriksson, Patrik John Gustav; Wu, Tong (Frontiers in Nutrition, 2018)
The industrialized world has entered a new era of widespread automation, and although this may create long-term gains in economic productivity and wealth accumulation, many professions are expected to disappear during the ensuing shift, leading to potentially significant disruptions in labor markets and associated socioeconomic difficulties. Food production, like many other industrial sectors, has also undergone a century of mechanization, having moved towards increasingly large-scale monoculture production – especially in developed economies – with higher yields but detrimental environmental impacts on a global scale. Certain characteristics of the food sector and its products cast doubts on whether future automation will influence it in the same ways as in other sectors. We conceptualize a model of future food production within the socioeconomic conditions created by widespread automation. We argue that despite immediate shocks to the economy, in the long run higher productivity can free up human activity to be channeled towards more interactive, skill-intensive food production systems, where communal efforts can reduce industrial reliance, diversify farming, and reconnect people to the biosphere – a realization of human well-being that resembles the classical philosophical ideal of Eudaimonia. We explore food production concepts such as communal gardens and polyculture, and the economic conditions and institutions needed to underwrite them (e.g., a universal basic income (UBI)). However, arguments can be raised as to why social-ecological systems would benefit from more labor-intensive food production. In this paper we: 1) discuss the current state of the food system and the need to reform it in light of its environmental and social impacts; 2) present automation as a lever that could move society towards more sustainable food production; 3) highlight the beneficial attributes of a Eudaimonian model; and 4) discuss the potential challenges to its implementation. Our purpose is to highlight a possible outcome that future research will need to refine and expand based on evidence and successful case studies. The ultimate aim is to promote a food system that can provide food security while staying within the safe operating space of planetary boundaries, produce more nutritious diets, enhance social capital, and reconnect communities with the biosphere.